Turn on the light on science A research-based guide to break down popular stereotypes about science and scientists - Tintori, Antonio (Ubiquity Press, 2017)
"Scientists deserve public recognition. The ways that they are depicted, however, are severely limited in physical and personal traits, helping to establish and enhance stereotypes under the general title of 'scientist'. These stereotypes range from the arrogant researcher who wants to rule the world, to the lab coat wearing 'nerdy' genius, but all generally fall to an extreme view of an existing perception of what a scientist should look and be like. For example, the popular image of 'a scientist' overlooks the presence of women almost entirely unless attributed to specific subjects and/or with narrow character depictions. The implications can be far-reaching. Young people, being heavily swayed by what they see and hear in the media, may avoid scientific careers because of these limited or unflattering portrayals of the scientific community, regardless of whether they reflect real life. Based on findings from the Light'13 project, this book examines such stereotypes and questions whether it is possible to adjust people's perception of scientists and to increase interest in science and scientific careers through a series of specific actions and events."